2013
DOI: 10.1007/s11552-013-9557-y
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Education Level on Outcome after Distal Radius Fracture

Abstract: Background Socioeconomic factors have been found to be predictors of outcome for other ailments. The purpose of this study was to evaluate the association of patient education level on pain and disability after distal radius fracture. Methods A series of patients with distal radius fractures (n = 335) were enrolled into a prospective research registry. Standard demographic information was obtained from patients, including a five-value categorical education variable. After treatment with closed reduction, exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 31 publications
3
22
1
Order By: Relevance
“…A prospective case series of 227 adults with DRF treated operatively or nonoperatively and followed over 12 months after injury found that each increase in the level of education (eg, from high school to some college) doubled the rate of improvement over time in pain, wrist range of motion, grip strength, and disability. 116 This was because education is known to be a robust determinant of socioeconomic status, which in turn is highly associated with the outcomes among patients with DRF. 116 Moreover, highly educated people with DRF tend to change their jobs more easily to move to a work environment, which is less physically stressing in comparison to less educated patients who are often employed in low-income jobs requiring manual labor.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective case series of 227 adults with DRF treated operatively or nonoperatively and followed over 12 months after injury found that each increase in the level of education (eg, from high school to some college) doubled the rate of improvement over time in pain, wrist range of motion, grip strength, and disability. 116 This was because education is known to be a robust determinant of socioeconomic status, which in turn is highly associated with the outcomes among patients with DRF. 116 Moreover, highly educated people with DRF tend to change their jobs more easily to move to a work environment, which is less physically stressing in comparison to less educated patients who are often employed in low-income jobs requiring manual labor.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…116 This was because education is known to be a robust determinant of socioeconomic status, which in turn is highly associated with the outcomes among patients with DRF. 116 Moreover, highly educated people with DRF tend to change their jobs more easily to move to a work environment, which is less physically stressing in comparison to less educated patients who are often employed in low-income jobs requiring manual labor. 17 Also, it is possible that those with high levels of education (whether retired or employed) might be more financially stable and better able to access and adhere to rehabilitation therapy programs.…”
Section: Socioeconomic Factorsmentioning
confidence: 99%
“…The influence that SES has on healthcare has been widely recognized (75). Higher SES has been associated with a higher access to and utilization of surgical and pharmacological treatments as well as better outcomes after treatment (76)(77)(78)(79)(80). Education is probably the best single indicator representing SES (81,82).…”
Section: Socioeconomic Status and Symptomatic Surgerymentioning
confidence: 99%
“…All but 1 study was of moderate quality (SEQES score, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Lower levels of education were found to be associated with decreased range of motion 6 weeks after DRF in a prospective cohort study aimed to identify demographic, injury-related, or psychologic factors associated with finger stiffness at suture removal and 6 weeks after DRF surgery.…”
Section: Educationmentioning
confidence: 99%